In This Issue - Scriven, Michael (Journal of MultiDisciplinary Evaluation, 2005)
This is a particularly interesting issue, which is just as well since it’s also our longest to date—over 220 pages, and I doubt you can find a way to shorten it without a hundred readers feeling seriously deprived!